تجليات التناص في ديوان "بوابات النور" لعبد القادر بن محمد بن القاضي - سليماني حكيم (université msila, 2022)
النص الشعري عالم مفتوح على نصوص سابقة أو معاصرة له أدبية كانت أم غير أدبية، وعليه فإن هذا المقال يعرف بالشاعر الجزائري عبد القادر بن محمد بن القاضي وبديوانه"بوابات النور" ويبحث في شعره، ويحاول الكشف عن تجليات انفتاحه على النصوص السابقة وعلى النصوص المعاصرة له، وقد ارتأينا ترتيب الموضوع بالنظر إلى النصوص الغائبة التي استحضرها ممثلة في القرآن الكريم، ثم الشعر العربي القديم والحديث. The poetic text is a world open to previous or contemporary texts, whether literary or non-literary. Therefore, this article is known as the Algerian poet Abdelkader bin Muhammad bin al-Qadi and his collection poetry “Gates of Light” ;researches his poetry, and attempts to reveal the manifestations of his openness to previous texts and contemporary texts. We have decided to arrange the subject by looking at the absent texts that he brought up represented in the Holy Qur’an, then ancient and modern Arabic poetry
Keywords: التناص ; تجليات ; انفتاح ; النص الشعري ; النصوص الغائبة